Asas Cepat, Sederhana, dan Biaya Ringan dalam Praktik E-Court: Analisis Efektivitas Implementasi Digitalisasi Sistem Peradilan di Indonesia - Delvi Eka Ariyanti; Sidi Ahyar Wiraguna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The digital transformation of Indonesia’s judiciary through the e-Court system represents a Supreme Court initiative to realize the principles of speed, simplicity, and affordability as mandated by Article 2(4) of Law No. 48 of 2009 on Judicial Power. This study aims to analyze the effectiveness of these principles in the implementation of e-Court, particularly in civil cases at District Courts. The research employs a juridical-normative and juridical-empirical approach, collecting data through literature review, document analysis, and interviews with court officials, lawyers, and litigants. The findings indicate that e- Court significantly accelerates case administration, claim submission, and inter-party communication, reflecting a faster and more efficient adjudication process. Nevertheless, challenges remain, including technological infrastructure limitations, digital literacy disparities, and regional inconsistencies in implementation. Furthermore, although case fees have become more affordable, accessibility for people in remote areas continues to hinder procedural simplicity. The study concludes that e-Court has positively contributed to realizing the principles of speed, simplicity, and low cost, yet further policy reinforcement, equitable digital infrastructure, and human resource development are necessary to achieve an inclusive and just digital judiciary.